SCARCITY, TIME, AND HUMAN PURPOSE: AN ISLAMIC ECONOMIC FRAMEWORK DERIVED FROM SURAH AL-‘ASR - Aris Anwaril Muttaqin; Nisrina Iftinan Naila; Muhammad Iqbal; Aisyah Tsabita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The scarcity of resources, a crucial concept in conventional economics, has been a matter of debate among Muslim economists. Some of them argue that the resources available in the world are limited. Others argue that the resources provided by Allah SWT are abundant. Although studies explaining the scarcity of resources in Islam have been conducted, existing studies do not connect with the evidence found in Surah al-Asr. Imam Syafi'i stated that if Muslims contemplated the contents of this surah, its guidance would suffice them. This study aims to analyse the scarcity of resources and their allocation based on evidence found in Surah al-Asr. This study was conducted using a qualitative approach, using Surah al-Asr and its interpretation as primary data. Apart from taking the main references from tafseer books, interpretation is also carried out by involving economists and Islamic finance practitioners through interviews. The results of the study show that resources are a gift from Allah SWT to humans. Surah al-Asr explains the scarcity of resources in the form of time provided by Allah SWT in this world. Scarcity of resources need to be distributed to achieve maslahat (benefits) in the form of faith, good deeds and mutual assistance between economic agents. Thus, this study recommends a framework of thinking from the revelation taught by God to formulate the scarcity of resources and their allocation in the development of the Islamic economic system.